DIAGNOSTIC ACCURACY OF CHEST RADIOGRAPH IN INTERSTITIAL LUNG DISEASE AS CONFIRMED BY HIGH-RESOLUTION COMPUTED TOMOGRAPHY (HRCT) CHEST - Faiza Akram; Shahid Hussain; Ali, Azmat; Hamza Javed; Muhammad Fayyaz; Khalil Ahmed (Journal of Ayub Medical College Abbottabad, 2022)
Background: Interstitial Lung Disease (ILD) - an umbrella term encompassing about 100 different pathophysiological entities are usually defined as an irreversible, progressive fibrotic changes in the lung parenchyma that leads to difficult breathing and reduced gaseous exchange at the alveolar level. We aimed to quantify the validity of CXR for the diagnosis of ILD taking HRCT as gold standard in the population of Hazara division. Methods: This validation study was conducted during 11 June till 12 Dec 2019 in the radiology department of Ayub Teaching Hospital, Abbottabad on 60 adult patients aged 30-60 years who presented with progressive exertional dyspnoea. The patients were enrolled into the study via non-probability, consecutive sampling technique. All the data was recorded on a self-developed structured questionnaire. Data was analyzed using SPSS version 20. Results: The mean age of study participants was 47.18±6.90 years SD with a range of 36-60years. The mean of time duration of symptoms was 9.66±1.7 years with a range of 7-12 years. There were 40 (66.7%) males and 20 (33.3%) females with a male to female ratio of 2:1. The sensitivity, specificity, PPV, NPV and Diagnostic Accuracy of CXR for the diagnosis of ILD as compared to HRCT was calculated to be 65.5%, 20%, 90%, 5% and 61.66% respectively. A chi square test of significance yielded a value of 0.51 for the diagnostic accuracy of CXR for ILD as compared to HRCT. Diagnostic ODDs ratio and Youden’s Index yielded values of 47.37% and 0.145 respectively. All these parameters’ points towards a lower utility of CXR for the diagnostic purpose in patients suspected with ILD. Conclusion: Chest x-ray is simple, non-invasive, economical and readily available alternative to HRCT but its specificity and diagnostic accuracy are questionable. CXR is a recommendable first line investigation for chest pathology workup but for a definitive diagnosis, one should not depend on CXR as it can miss the diagnosis.